PENGARUH KINERJA PEGAWAI DAN SISTEM INFORMASI KEUANGAN TERHADAP AKUNTABILITAS KEUANGAN DESA DI KECAMATAN PONRANG - Nurpadillah; Patra, A. Dahri Adi Patra; Usman, Halim Usman (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research aims to examine employee performance and financial information systems on financial accountability in villages in the Ponrang sub-district. This type of research is quantitative research. The data collection method in this research used a questionnaire with the population being village office employees in Ponrang sub-district. The sample used in this research was 60 which was determined using the Slovin formula, the analysis method used was validity test, reliability test, classical assumption test, hypothesis test, and linear regression test. The results of the research show that: in this research, there is a partial influence of employee performance on village financial accountability in Ponrang District, so that the first hypothesis in this research is accepted. Partially there is no influence of the financial information system on village financial accountability in Ponrang District, so the second hypothesis in this research is rejected. Simultaneously there is an influence of employee performance and financial information systems on village financial accountability in Ponrang District.